Hobbs & Shaw [videorecording (DVD)] - Johnson, Dwayne, 1972-; Statham, Jason, 1967-; Elba, Idris; Kirby, Vanessa; González, Eiza, 1990-; Curtis, Cliff, 1968-; Mirren, Helen (Universal Pictures Home Entertainment, 2019)
Ever since hulking lawman Hobbs, a loyal agent of America's Diplomatic Security Service, and lawless outcast Shaw, a former British military elite operative, first faced off, the duo have swapped smack talk and body blows as they've tried to take each other down. But when anarchist Brixton gains control of an insidious bio-threat that could alter humanity forever, these two sworn enemies will have to partner up to bring down the only guy who might be badder than themselves.